Storage stability of texture, organoleptic, and biological properties of goat milk yogurt fermented with probiotic bacteria - Yang, Yaling; Zhang, Ruyue; Zhang, Fuxin; Wang, Bini; Liu, Yufang (Frontiers in Nutrition, 2023)
In this study, goat yogurt was fermented with four probiotics, respectively, including Lactobacillus acidophilus (GYA), Bifidobacterium animalis (GYB), Lactobacillus casei (GYC) and Lactobacillus plantarum (GYP), and tested for texture, organoleptic, and biological properties during a 4-week storage period at the refrigerated temperature. All goat yogurt with probiotics showed an increase on titratable acidity and a corresponding downward trend on pH value. Viable counts of L. acidophilus and L. casei were above 6 log cfu/mL at the end of the storage, which met the minimum standards for viable probiotic bacteria in yogurt specified by the FAO. The texture and organoleptic characteristics of fermented goat milk depended on the strain and the storage period. DPPH free radical scavenging rate and ferric reducing antioxidant power activity gradually increased in all goat yogurts during the storage and yogurt with probiotic bacteria showed higher values than those of GY0. Among all probiotic containing goat yogurts, GYC exhibited the desirable characteristics of hardness, adhesiveness, water holding capacity, antioxidant activity during the whole storage. Furthermore, the addition of L. casei effectively weakened the goaty flavor and enhanced the overall acceptability. Thus, fermented goat milk with L. casei is optional for the development of goat milk product with satisfactory texture properties, pleasant sensory quality and high bioactivity.